Windblown sediment transport and loss in a desert–oasis ecotone in the Tarim Basin - Huawei Pi (Nature Portfolio, 2017)
Abstract The Tarim Basin is regarded as one of the most highly erodible areas in China. Desert comprises 64% of the land use in the Basin, but the desert–oasis ecotone plays a prominent role in maintaining oasis ecological security and stability. Yet, little is known concerning the magnitude of windblown sediment transport in a desert-oasis ecotone. Therefore, aeolian sediment transport and loss was assessed from a desert-oasis experimental site located near Alaer City in the northwestern Tarim Basin. Sediment transport and factors governing transport were measured during three high wind events in 2012 and four events in 2013. Sediment transport was measured to a height of 10 m using passive aeolian airborne sediment samplers. The mass flux profile over the eroding surface was well represented by the power-law (R2 > 0.77). Sediment loss from the site ranged from 118 g m−2 for the 20–24Apr 2012 wind event to 2925 g m−2 for the 31Mar–11Apr 2012 event. Suspension accounted for 67.4 to 84.8% of sediment loss across all high wind events. Our results indicate the severity of wind erosion in a desert-oasis ecotone and thus encourage adoption of management practices that will enhance oasis ecological security.